2013
DOI: 10.3389/fnbeh.2013.00127
|View full text |Cite
|
Sign up to set email alerts
|

Stress affects theta activity in limbic networks and impairs novelty-induced exploration and familiarization

Abstract: Exposure to a novel environment triggers the response of several brain areas that regulate emotional behaviors. Here, we studied theta oscillations within the hippocampus (HPC)-amygdala (AMY)-medial prefrontal cortex (mPFC) network in exploration of a novel environment and subsequent familiarization through repeated exposures to that same environment; in addition, we assessed how concomitant stress exposure could disrupt this activity and impair both behavioral processes. Local field potentials (LFP) were simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 48 publications
9
48
0
Order By: Relevance
“…Notably, stress exposure shifted LC-mPFC coherence to a distinct frequency range (7-9 Hz) regardless of day or age. As coherence between the mPFC and other brain regions within the theta range has been implicated in fear memory (Jacinto et al, 2013;Lesting et al, 2013), the current study provides evidence that the LC also participates in this anxiogenic neural circuit. At the same time that repeated stress enhanced LC-mPFC theta coherence, it impaired coherence at higher frequencies (eg, gamma) that have been implicated in higher cognitive processing, selectively in adolescent rats (Benchenane et al, 2011).…”
Section: Social Stress and Lc Network Activitymentioning
confidence: 70%
“…Notably, stress exposure shifted LC-mPFC coherence to a distinct frequency range (7-9 Hz) regardless of day or age. As coherence between the mPFC and other brain regions within the theta range has been implicated in fear memory (Jacinto et al, 2013;Lesting et al, 2013), the current study provides evidence that the LC also participates in this anxiogenic neural circuit. At the same time that repeated stress enhanced LC-mPFC theta coherence, it impaired coherence at higher frequencies (eg, gamma) that have been implicated in higher cognitive processing, selectively in adolescent rats (Benchenane et al, 2011).…”
Section: Social Stress and Lc Network Activitymentioning
confidence: 70%
“…Indeed, in rodent models of stress (Jacinto et al, 2013; Oliveira et al, 2013) and schizophrenia (Sigurdsson et al, 2010) coherences between VH and PFC are decreased. Likewise, the majority of studies in children with ASD have demonstrated reduced coherences (Coben et al, 2008; Khan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is a structure that plays a pivotal role in anxiety and emotional-motivated behaviors (Jacinto et al, 2013). In fact, exposure to new environments elicits anxiety-driven defensive behaviors in rats (Gray and McNaughton, 1996).…”
Section: Discussionmentioning
confidence: 99%